Discursividades sobre a EJA do Estado de Goiás: a voz dos professores e dos documentos oficiais em análise - (:unkn) unknown (Universidade Federal de Goiás, 2015)
This research proposes to investigate the sayings of Portuguese subjects teachers of the Youth and Adult Education of the state of Goiás in relation to both official documents of the state: the Curriculum Guidelines of Youth and Adult Education in the state of Goiás and Curriculum Matrices of Portuguese Language: First and Second Steps - Elementary School. For this, we put in a discursive arena the various voices coming from the school practice and public institutional politics. We collected sayings of ten teachers of public institutions that work with this teaching modality being they subjects teachers from different cities, that are under the jurisdiction of Regional Secretariats of Morrinhos, Catalão, Itumbiara, Pires do Rio and Piracanjuba. Were analyzed, in the cutted sequences, discursive recurrences that characterize the says of the subjects surveyed in an alterity relation with the subject student. As theoretical support, we resort to Bakhtin Circle and the French Discourse Analysis, of Pêcheux, to discuss some fundamental concepts of dialogical relations such as subject, language conception, alterity and dialogue. Other discussions have taken place having as reference Michel Foucault, in which we based the discussions about the relations of knowledge and power. Also we describe the effects of meaning coming of discursive and social practices that involve Youth and Adult Education. Is worth mentioning that our theoretical research used the proposal of Resonances Discourse Analysis in Open Testimonials, of Serrani-Infante (1998), for the data collect, transcription of the collected testimonies, and the analysis of the corpus. This allowed us to auscultation of different voices with which the subject teacher of Portuguese of Youth and Adult Education dialogues, resonating, thus, a representation that the teacher has about himself, that is built on the relation to the other, being permeated by the discourse of psychology, of the neoliberal discourse and relations of knowledge and power. At various points, the institutional discourse constituted in the arena socio-discursive converges to the same discursive formation of teachers, because they subscribe in an imaginary formation, in which the student of EJA is idealized, and therefore, the teacher is too. In the order of discourse of the documents, there is the prescription in order to convince teachers to have determined teaching practices. However, they position themselves axiologically, revealing a practice of teaching that considerate the needs of their students by introducing a teacher who responds to the other and that is responsible for taking the ethical position.
Discursivities about EJA the state of Goiás: the voice of teachers and official documents en review
Keywords: Discurso; Diálogo; Educação de jovens e adultos; Sujeito; Relações de saber-poder; Língua Portuguesa; Discourse; Dialogue; Youth and adult education; Subject; Relations of knowledge-power; Portuguese; LINGUISTICA, LETRAS E ARTES